Diffusion-weighted imaging with calculated apparent diffusion coefficient of enhancing extra-axial masses. - Dorenbeck, U; Grunwald, I; Schlaier, J; Feuerbach, S (2005)
BACKGROUND AND PURPOSE: Sometimes intracranial contrast-enhancing tumors like meningiomas, metastases, lymphomas, and schwannomas can mimic each other. It was the aim of the present study to investigate if intracranial contrast-enhancing lesions can be reliably differentiated with the help of diffusion-weighted imaging with calculated apparent diffusion coefficients (ADCs). METHODS: 29 patients (ages ranging from 22 to 82 years, mean age of 58.6 years) were included. Nine meningiomas, 7 metastases, 6 lymphomas, and 7 schwannomas were investigated. The ADC value in the lesions and in the perifocal edema was analyzed. RESULTS: For the lymphomas, the authors measured the lowest ADC values in the contrast-enhancing part (0.59 +/- 0.09 . 10(-3) mm2/sec). The meningiomas showed a mean ADC value of 0.98 +/- 0.18 . 10(-3) mm2/sec. The schwannomas and metastases showed higher ADC values of 1.33 +/- 0.28 . 10(-3) mm2/sec and 1.05 +/- 0.20 . 10(-3) mm2/sec. The authors saw a statistically significant difference between lymphomas, meningiomas, and metastases concerning the ADC values in the contrast-enhancing part. CONCLUSIONS: In spite of a small sample size and partly a wide range of values, the authors found statistically significant differences between meningiomas, metastases, and lymphomas concerning ADC values. Nevertheless, a differentiation of these lesions only with the help of ADC values seems questionable.